Fatima Mernissi's Criticism of Misogynistic Hadiths Related to Gender Equality in The Modern Era - Syafitri, Fauziah (Institut Agama Islam Negeri Ponorogo, 2024)
The researcher aims to present a paper related to the criticisms raised by Fatima Mernissi against gender-biased misogyny traditions in accordance with her thoughts. Gender equality is a very hot issue discussed today. Equality of rights between men and women is increasingly being voiced. This also happens within the scope of Islam. The emergence of discussions about misogynistic traditions is also increasingly highlighted, especially by Fatima Mernissi who focuses on issues of gender equality. This research method uses a literature review of various relevant articles. The results of this study show that Fatima Mernissi criticizes gender-biased hadiths to be contextualized according to the conditions and situations of the times. This is to provide space for women to be more free in running their lives without being intervened by patriarchy. The importance of contextualization in understanding traditions is very important, so that all Muslims can live life better and there are no practices that override women's rights.